Influence of mesh discretization on the prediction of polymer flow behaviour in microcavities - Zhiltsova, T. V. (2013)
Microinjection moulding is one of the key technologies for the mass production of plastics microcomponents. Recently, significant effort has been made to test the limits of applicability of existent numerical codes for simulating the polymer flow at the microscale. However, the modelling precision in what concerns polymer flow in microimpressions depends on factors which may not be properly accounted for in the process simulation. In this study, a micropart with variable thickness was designed, and the moulding block fabricated and instrumented. Short shots and complete filling of the cavity were carried out and the flow front progress was subsequently evaluated. These data were also assessed numerically by 3D-finite element modelling. A flow simulation considering the polymer as incompressible was carried out to investigate how the mesh size and density affected the prediction of the flow field in the microimpression, using the same processing conditions of the experimental study. The reduction of the mesh size as well as the increase of the mesh density are consistent with better representativeness of the experimental flow front progress in the microimpression. Moreover, the weld line prediction also tends to be improved. This study suggests that the mesh adaption and domain discretization is important in numerical studies of the polymer flow at the microscale.